ANALISIS SEMIOTIK TIGA FOTO ESSAY PEKAN INI PADA SURAT KABAR KOMPAS - Maria Jashinta Elisabet Hamboer; Iswahyu Pranawukir (FISIP IBI-K57 Prodi Komunikasi, 2020)
The main problem of this research is, how to know the hidden meaning of photo essay from social and psychological aspects. The purpose of this research itself is to find out the hidden meanings in the essay photo, apart from what is visible. This study uses a qualitative descriptive method, which is a method that aims to provide as accurate a picture as possible of the characteristics of an individual, the characteristics of a group or individual society as well as to find out and examine the characteristics of interest. With the data analysis technique, namely the semiotic analysis model used by Roland Barthes (1990), namely, analyzing the sign. In this model, the main idea is focused on the two-stage significance (two order signification). Data collection was obtained through literature study accompanied by interviews with a photography. The results of this study indicate that in the photo essay there is a hidden meaning from a social and psychological perspective.